2021
DOI: 10.7717/peerj.11938
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of BpDof genes and the tolerance to drought stress in birch (Betula platyphylla)

Abstract: Background DNA binding with one finger (Dof) proteins are plant-specific transcription factors playing vital roles in developmental processes and stress responses in plants. Nevertheless, the characterizations, expression patterns, and functions of the Dof family under drought stress (a key determinant of plant physiology and metabolic homeostasis) in woody plants remain unclear. Methods The birch (Betula platyphylla var. mandshuric) genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Therefore, exploring key drought-tolerance genes and creating drought-resistant germplasm is urgent. Dof is a classic protein of the zinc finger family that regulates multiple biological functions and responds to abiotic stress in plants (Sun et al 2021). Recently, the Dof family has been systematically studied at the genome-wide level in many plant species; however, the molecular mechanisms of ZmDofs in maize are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exploring key drought-tolerance genes and creating drought-resistant germplasm is urgent. Dof is a classic protein of the zinc finger family that regulates multiple biological functions and responds to abiotic stress in plants (Sun et al 2021). Recently, the Dof family has been systematically studied at the genome-wide level in many plant species; however, the molecular mechanisms of ZmDofs in maize are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, MdDOF54 could improve the drought tolerance of plants. Similarly, overexpression of the birch BpDOF4, BpDOF11, and BpDOF17 genes improved drought tolerance by enhancing the ROS scavenging ability (Sun et al, 2021). Notably, DOF proteins can also improve plant survivability in extreme temperature environments.…”
Section: Responses Of Dofs To Biotic and Abiotic Stressesmentioning
confidence: 99%
“…Earlier studies identified 37 DOF members in Arabidopsis thaliana, one of which is a pseudogene (Yanagisawa, 2002), while 30 DOF members were identified in rice (Oryza sativa) (Lijavetzky et al, 2003). With the analysis of the whole genomes of many species, an increasing number of DOF members have been identified in different species (Table 1), including 26 DOF genes in birch (Betula platyphylla) (Sun et al, 2021), 36 in watermelon (Citrullus lanatus) (Zhou et al, 2020), 35 in foxtail millet (Setaria italica) (Zhang et al, 2017), 22 in spinach (Spinacia oleracea) (Yu et al, 2021a) and 24 in rose (Rosa chinensis) (Nan et al, 2021). Despite the species differences, the functions of DOF members in the monocot model plant rice are still questioned.…”
Section: Origin and Evolution Of Dof Tfsmentioning
confidence: 99%
See 1 more Smart Citation
“…In monocot plants, Eleusine coracana (48 individuals), Musa acuminata (74 individuals), and Setaria italica (35 individuals) had been identified ( Dong et al, 2016 ; Zhang et al, 2017 ; Gupta et al, 2018 ). In dicotyledonous plants, A. thaliana (39 individuals), i (60 individuals), Populus trichocarpa (41 individuals), and Betula platyphylla (26 individuals) had been identified ( Le Hir and Bellini, 2013 ; Wang et al, 2017 ; Zhang et al, 2017 ; Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%